Pengaruh Sholat Tahajud dalam Meningkatkan Kecerdasan Spiritual Remaja di Pondok Pesantren Assudaniyah, Medan - Daeli, Alvi Syahri (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2023)
Three categories of intelligence are used to describe youth: IQ (intellectual ability), EQ (emotional aptitude), and SI (spiritual ability). (SQ). The author here places more emphasis on spiritual intelligence. (SQ). In general, a teenager at this age must have spiritual intelligence that is obtained through closeness to Allah SWT, one of which is by reading the Tahajud Prayer. A teenager at this age is not enough just to have academic intelligence or emotional intelligence. In this regard, the author wants to know more about the influence of midnight prayers at the Assudaniyah Islamic Boarding School in Medan on the spiritual intelligence of adolescents. Qualitative techniques are used when conducting field and library research. Direct observation at the Assudaniyah Islamic Boarding School in Medan, interviews with related parties, and documentation are the methods used to collect data in this study. The results of this study: Assudaniyah Islamic Boarding School has a major role in Improving Youth Spiritual Intelligence through Tahajud Prayers through the implementation of prayer activities with several processes carried out including through exemplary, training and habituation, dialogue, discipline and Mau'izhah. Then there are also factors that become obstacles and supports to increase the spiritual intelligence of adolescents at the Assudaniyah Islamic boarding school, Medan. From this elaboration the author takes several important points about the effect of midnight prayers at the Assudaniah Islamic Boarding School, including: Increasing Faith in Allah SWT, Increasing Santri Discipline, Having a Happy Spirit so as to give birth to productive teenagers, Increasing peace of mind, Stabilizing adolescent self-emotions, Forming The noble character of Santri/Adolescents and Improving the Condition of the brain and learning motivation of students.Keywords: Midnight Prayer, Spiritual Intelligence (SQ), Islamic Boarding School.